Dispersal of Silica-Scaled Chrysophytes in Northern Water Bodies - Anna Bessudova; Yurij Bukin; Yelena Likhoshway (Diversity, 2021)
Silica-scaled chrysophytes have an ancient origin; nowadays they inhabit many northern water bodies. As the territories above the 60th parallel north were under the influence of glaciers during the Late Pleistocene, the local water bodies and their microalgal populations formed mainly during the Early Holocene. Now, the arctic, sub-arctic and temperate zones are located here and the water bodies in these regions have varying environmental characteristics. We analyzed the dispersal of silica-scaled chrysophytes in 193 water bodies in 21 northern regions, and for 135 of them determined the role of diverse environmental factors in their species composition and richness using statistical methods. Although the species composition and richness certainly depend on water body location, water temperature and conductivity, regions and individual water bodies with similar species composition can be significantly distant in latitudinal direction. Eighteen species and one variety from 165 taxa occurring here have clear affinities to fossil congeners; they have been encountered in all regions studied and amount to 6–54% of the total number of silica-scaled chrysophytes. We also compared the distribution of the species with a reconstruction of glacier-dammed lakes in the Northern Hemisphere in the Late Pleistocene–Early Holocene. The dispersal of silica-scaled chrysophytes in the northern water bodies could take place in the Late Pleistocene–Early Holocene over the circumpolar freshwater network of glacier-dammed lakes, the final Protista composition being subject to the environmental parameters of each individual water body and the region where the water body is located. This species dispersal scenario can also be valid for other microscopic aquatic organisms as well as for southerly water bodies of the Northern Hemisphere.